Birth Registration in the Developing World: Bridging the gap between policy and practice - Abu S. Shonchoy; Zaki Wahhaj (LSE International Development, 2023)
Birth registration is a fundamental human right, yet millions of children worldwide still lack this crucial documentation. Even though the United Nations Convention on the Rights of the Child emphasizes immediate registration after birth, the reality on the ground is quite different.
Keywords: 2023-10 October